Anodic Materials for Lithium-ion Batteries: TiO2-rGO Composites for High Power Applications. (10th March 2017) - Minella, M.; Versaci, D.; Casino, S.; Di Lupo, F.; Minero, C.; Battiato, A.; Penazzi, N.; Bodoardo, S.
Graphical abstract: Abstract: Titanium dioxide/reduced graphene oxide (TiO2 -rGO) composites were synthesized at different loadings of carbonaceous phase, characterized and used as anode materials in Lithium-ion cells, focusing not only on the high rate capability but also on the simplicity and low cost of the electrode production. It was therefore chosen to use commercial TiO2, GO was synthesized from graphite, adsorbed onto TiO2 and reduced to rGO following a chemical, a photocatalytic and an in situ photocatalytic procedure. The synthesized materials were in-depth characterized with a multi-technique approach and the electrochemical performances were correlated i ) to an effective reduction of the GO oxidized moieties and ii ) to the maintenance of the 2D geometry of the final graphenic structure observed. TiO2 -rGO obtained with the first two procedures showed good cycle stability, high capacity and impressive rate capability particularly at 10% GO loading. The photocatalytic reduction applied in situ on preassembled electrodes showed similarly good results reaching the goal of a further simplification of the anode production.